2021
DOI: 10.1111/ijcp.15003
|View full text |Cite
|
Sign up to set email alerts
|

The profile of the causative organisms which lead to septic arthritis of native joints over the last two decades in a single tertiary medical center in the east coast of the United States

Abstract: Background: Septic arthritis (SA) is associated with significant morbidity and mortality. Delayed or inadequate treatment may result in joint destruction, osteomyelitis and sepsis. Like other types of infection, the causative agents of SA may have changed over time. Early targeted intervention is important in cases of SA and can be achieved only by understanding the current trends in the microbiology of SA.Objectives: To determine the trends in the microbiology of SA over the last two decades. Methods:We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Most BJI were due to Gram‐positive cocci, followed by aerobic Gram‐negative bacilli, consistent with data in the general population 18,28–35 . Overall, S. aureus , Streptococcus spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Most BJI were due to Gram‐positive cocci, followed by aerobic Gram‐negative bacilli, consistent with data in the general population 18,28–35 . Overall, S. aureus , Streptococcus spp.…”
Section: Discussionsupporting
confidence: 87%
“…Most BJI were due to Gram‐positive cocci, followed by aerobic Gram‐negative bacilli, consistent with data in the general population. 18 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Overall, S. aureus , Streptococcus spp. and Enterobacterales represented the vast majority of pathogens identified.…”
Section: Discussionmentioning
confidence: 99%
“…The causative organisms in this study were predominantly Gram-positive bacteria, with S. aureus and Streptococci attributable for more than 80% of these cases. MRSA was accountable for septic arthritis in more than half of the patients with bacteremia (58.3%) and in almost half of the patients who had positive synovial fluid cultures (47.6%)—both of these prevalence rates were higher than that of the general population [ 4 , 28 , 29 ]. The incidence rate of MRSA infection in dialysis patients in this study is noticeably higher than the rates reported in septic arthritis studies with or without dialysis status [ 9 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common locations for septic arthritis include shoulders, hips, and knee joints, all involving metaphyses with ample blood supply, which leads to the proclivity for bacterial infection [ 3 ]. The most frequently identified causative organism in septic arthritis is Staphylococcus aureus ( S. aureus ), followed by methicillin-resistant S. aureus (MRSA), Group B Streptococcus , and Gram-negative organisms [ 4 , 5 ]. The risk factors for the development of septic arthritis include an age greater than 80 years, diabetes mellitus, rheumatoid arthritis, recent joint surgery, hip or knee prosthesis and/or skin infection, and human immunodeficiency virus type-1 infection as suggested by meta-analysis research [ 6 ].…”
Section: Introductionmentioning
confidence: 99%